Public Health Effects of Radioactive Airborne Effluents from Nuclear and Coal-Fired Power Plant - Boldsaikhan Purevsuren; Juyoul Kim (Science and Technology of Nuclear Installations)
It has been well known that nuclear power plant and coal-fired power plant release some amount of radioactive materials during their normal operations. The purpose of this study was to compare radiation exposure doses to the public as a consequence of airborne effluents released from nuclear and coal-fired power plants under the normal operation. NRCDose3 was used to estimate radiation exposure doses to the public from gaseous effluents of nuclear power plant during its normal operation while CAP88-PC was used to calculate doses to the public living around coal-fired power plant. The results showed that radiation exposure doses from nuclear power plant were less than those from coal-fired power plant and regulatory annual limits. Effective dose by external exposure, skin equivalent dose, and organ equivalent dose from gaseous effluents of nuclear power plant were 2.93 × 10−4 mSv/y, 2.90 × 10−3 mSv/y, and 1.78 × 10−2 mSv/y, respectively. On the contrary, the corresponding effective dose by external exposure, external skin dose, and organ dose from coal-fired power plant were 1.13 × 10−2 mSv/y, 5.33 × 10−2 mSv/y, and 1.17 × 10−1 mSv/y, respectively.